Aniceto, el vencecanguelos - Armijo, Consuelo; Puncel, Margarita (Madrid : Ediciones SM, 2000)
Aniceto is a fearful boy who has a rich imagination. He has to confront fears such as a visit from his aunt and uncle, a small airplane ride, the ridicule of friends, and even his chemistry teacher. When Aniceto excels at his first job, he becomes a more mature person.
A partir de 7 a?os.
Premio C.C.E.I., 1982.
Premio Lazarillo, 1974.
Premio El Barco de Vapor, 1978.
Premio C.C.E.I., 1982.
Premio Lazarillo, 1974.
Keywords: Fear -- Juvenile fiction; Miedo -- Novela juvenil